The (Non-)Effect of Violence on Education : Evidence from the War on Drugs in Mexico - Márquez-Padilla, Fernanda (2015)
This paper studies the sharp increase in violence experienced in Mexico after 2006, known as The War on Drugs, and its effects on human capital accumulation. The upsurge in violence is expected to have direct effects on individuals schooling decisions, but not indirect effects, because there was no severe destruction of infrastructure. The fact that the marked increases in violence were concentrated in some municipalities (and not in others) allows for implementation of a fixed-effects methodology to study the effects of violence on educational outcomes. Different from several recent studies that have found significant negative effects of violence on economic outcomes in Mexico, the paper finds evidence that this is not the case, at least for human capital accumulation. The paper uses several sources of data on homicides and educational outcomes and shows that, at most, there are very small effects on total enrollment. These small effects may be driven by some students being displaced from high-violence municipalities to low-violence municipalities; but the education decisions of individuals do not seem to be highly impacted. The analysis discards the possibility that the effects on enrollment of young adults appear small because of a counteracting effect from ex-workers returning to school. The results stand in contrast with recent evidence of the negative effects of violence on short-term economic growth, since minimal to 0 effects on human capital accumulation today should have little to no adverse effects on long-term growth outcomes in Mexico.